(untitled) (Texas Journal of Engineering and Technology, 2022)
In the past tense, studies relating to concrete with high performance have shown the harmful role of excess water in concrete. The reduction of this quantity of water, by using deflocculates and by correcting granular stacking via ultrafine, has led to gains in strength and known durability. As an extension of this scientific work, the observed improvement in the workability of these new concretes led the researchers to develop and make this property reliable. Today, in total continuity with high-performance concretes, it is a change of objectives constituting a veritable cultural revolution proposed by the self-compacting concretes: the study of the material is no longer governed solely by improving resistance and durability. However, these latter properties remain wedged at levels equivalent to or higher than those of joint concretes. In this area now, with self-compacting concretes, the ability to be easily placed work without vibration which has become priorities. These skills will have great consequences in terms of execution time, reduction of materials, quality of concreting, ease of implementation, respect for the neighborhood, and less hardship for the workers